The Impact of Informal Cross-Border Trade on Kenya-Uganda Foreign Relations - Atozo, Zachariah Onditi; Ndalilah, Joseph W. (Utafiti Foundation, 2024)
This paper generally discusses the intricate dynamics of Informal Cross-Border Trade (ICBT) and its profound impact on Kenya-Uganda foreign relations. It is observed in this study that, Kenya and Uganda share a similar history, geography and a distinct cultural background, key to their social and economic relations. It is further noted that Kenya plays a significant role in Uganda's history and vice versa, sometimes influencing each other. Both countries are significant trading partners, but mostly informally, which has expanded in the post-independence period. This is attributed to their shared history, culture, and geography. Since the pre-colonial period, communities in the geographical area that came to be defined as the border between the two countries engaged in informal trade. The paper holds that, Informal Cross Border Trade along the Kenya-Uganda border has shaped the foreign relations between the two countries. The study applied territoriality theory to interpret the impact of ICBT on Kenya-Uganda foreign relations. The theory holds that, each sovereign state has authority to manage resources within its borders. The study used both primary and secondary sources. This study demonstrates that ICBT, positively influences Kenya-Uganda foreign relations. It also expands knowledge on the impact of ICBT on foreign relations.